TINJAUAN HUKUM TERHADAP PELAKSANAAN REDISTRIBUSI TANAH PERTANIAN DI KABUPATEN PANGKAJENE KEPULAUAN: LEGAL REVIEW OF IMPLEMENTATION OF AGRICULTURAL REDISTRIBUTION IN PANGKAJENE KEPULAUAN REGENCY - Purnama, Anang Sigit; Makkawaru, Zulkifli; Tira, Andi (Faculty Of Law Bosowa University, 2020)
The purpose of this research is to find out the legal arrangements related to the redistribution of agricultural land in Indonesia and how the implementation of this agricultural land redistribution activity at Pangkajene Kepulauan Regency and to see the related obstacles in its implementation. The empirical juridical approach method is the research method used, and uses nonrandom sampling techniques, which are deliberately chosen with certain parameters. Research with primary data and secondary data that are assessed in quality by separating in the form of sentences that are in harmony with the subject matter being studied. The location of the assessment was carried out at the Pangkajene Kepulauan District Land Office and in the Biraeng Village, Minasatene District and Minasatene Village, Minasatene District. From the research results, it is known that the application of Government Regulation No. 224 of 1961 is not in line with current developments, so with the issuance of Presidential Regulation. Number 86 of 2018, could be a solution in solving cases that occur. Redistribution of Agricultural Land in Pangkajene Kepulauan Regency is well implemented. Although there are obstacles, namely the lack of good coordination between the regional government and the community and the target subject has not been designated as the recipient of agricultural land redistribution activities.